Diversidade de formigas (Hymenoptera : Formicidae) em um fragmento florestal urbano em Cuiabá, MT - Carvalho, Maria Teresa Campos (2017)
In this work the study of ant diversity was carried out in an urban forest fragment in the city of Cuiabá, near the Bonapaceta State Park, in the periods from February to April, corresponding to the rainy season and July to September to the drought period, whose objective was to identify the diversity of native ants, according to levels of anthropization of the fragment. The environments were sampled: A1) Cerrado native; A2) Zone Anthropized; A3) Transition Zone. In each environment, 15 pitfall traps distributed in a transect were used, equidistant 20 meters from each other, to collect ants in a period of seven days. The individuals collected were taxed and taxonomically identified at the genus and species level. They were used for analysis, Tukey's test, faunistic analyzes, Diversity Indexes, Equity, Similarity and Accumulation Curve of Species. The analyzes of variance for the number of species collected showed that there was no significant statistical difference between the transition and anthropic environments, while for the number of individuals, there was a significant difference between native and anthropized in the dry period. Fauna analyzes indicated the occurrence of five subfamilies, being Myrmicinae and Formicinae, the most representative in quantity of species, independent of the environment and periods analyzed. The species Solenopsis sp., Solenopsis invicta, Atta sexdens, Labidus praedator, Pheidole jelskii and Pheidole obscurithorax, were the most important in the faunistic analysis, due to the maximum classifications obtained in the items composing the index. Regarding the Soronsen Index, the transition and anthropized environment were similar among themselves, regardless of the period analyzed.